Uso e ocupação do solo o futuro da Praia do Futuro - Abreu Júnior, Pedro Itamar de (2005)
This work investigates land use and occupation alone the 6km of Future beach, at the east seaside of Fortaleza-Ceará, limited by the sea (Atlantic ocean), at one side; the road Trajano de Medeiros, the road Ismael Pordéus and the estuary of Cocó river, at Caça e Pesca beach.In this work we tried an historical account of the place as an attempt to better understand its present situation, aiming at amusing the reasons why the neighbor suburbs show much denser standards of land use and occupation than the Future beach. Interviews were made with the main agents within the area, from the irregular users to hotel owners. By making use of research concerning published news on local newspapers, it was possible to get data covering the last 40 years of the seaside place, as there is very few available literature or academic work related to it. The search for an interdisciplinary approach has adapted throughout this work, using systematic methodology, basically as the work, using the systemic methodology, basically as an attempt to get answers to natural environmental impacts, and use the dialectic methodology in order to formulate hypothesis to human environmental impacts, which together are determinant to the actual pattern of land use an occupation at Future beach. This research also aims to provide means for understanding of the area under study as well as being useful as tool for others to work with, where as all particular characteristics of the place can be taken into account and the notion of sustainable development be always sought. This research was made possible with the support of the national council for research and development (CNpq) and the Federal University of Ceará